Novas ferramentas para visualização georreferenciada de dados: uma integração entre R e Google Maps - Luís Gustavo Silva e Silva (2013)
This paper presents the development and functionalities of the aRouca package. The package proposes new visualizations of geocoded data and was originally created to explore data of health professionals. The main contribution of this work is the integration of visualization environments and languages such as SVG, KML, Google APIs and R. We developed new features as viewing bar charts, pie charts and images integrated into the KML language. In particular, we use Google Charts API for generating dynamic images as url in KML files. The package works integrated into the Arouca platform, a database system that aggregatesinformation about health professionals who work in the Brazilian National Health System, and it allows the user to view dynamic and interactive flow of health professionals throughout nationwide.